Расчетно-экспериментальное определение теплофизических характеристик материалов при экстремальных тепловых воздействиях - Веселовский, В. Б.; Беляева, Виктория Витальевна; Грибанова, А. В.; Кириченко, Р. А. (Национальный технический университет "Харьковский политехнический институт", 2011)
The mathematical model and computational methods of determination of bodies’ thermal physical parameters on the basis on experimental measurements by the laser flash method are presented. Solutions of unstationary heat conduction problem for constituent elements of construction with unified external boundary conditions and conditions of nonideal thermal contact were obtained. Results of computational xperiments are given.
Keywords: теплоперенос; тепловой удар; термическое напряжение